Mechanism of Cysteine Desulfurase Slr0387 from Synechocystis sp. PCC 6803: Kinetic Analysis of Cleavage of the Persulfide Intermediate by Chemical Reductants - Behshad, Elham; Parkin, Sara E; Bollinger, J. Martin (Biochemistry (Easton), 2004)
Cysteine desulfurases (CDs) are pyridoxal-5‘-phosphate (PLP)-dependent enzymes that cleave sulfur from cysteine via an enzyme cysteinyl persulfide intermediate. In vitro studies of these enzymes have generally employed dithiothreitol as a cosubstrate to reductively cleave the persulfide intermediate, and it has been suggested that persulfide cleavage is the rate-limiting step for catalysis. In this study, the kinetics and mechanisms of cleavage of the persulfide intermediate in Slr0387 (CD-0387), a sequence group I (NifS/IscS-like) cysteine desulfurase from Synechocystis sp. PCC 6803, by physiological and nonphysiological reductants have been examined, and the extent to which this step is rate-limiting for catalysis has been determined. The observations that dithiols such as dithiothreitol (DTT) cleave the persulfide with ∼100-fold greater efficiency than structurally similar monothiols such as 2-mercaptoethanol (2-ME), that cleavage by DTT exhibits saturation kinetics, and that the dependence of the observed first-order rate constant for persulfide cleavage by DTT on the concentration of the dithiol corresponds precisely with that for formation of a complex between DTT and the PLP cofactor of the resting enzyme suggest that persulfide cleavage by dithiols occurs by prior formation of a complex, in which addition of one thiol to the cofactor positions the second thiol for attack. This conclusion and the observation that a second molecule of l-cysteine can bind to the cofactor in the persulfide form of CD-0387 explain why several CDs are subject to potent inhibition by l-cysteine during turnover with DTT:  binding of l-cysteine prevents formation of the PLP−DTT adduct and renders the dithiol no better than a monothiol, which must react with the persulfide in bimolecular fashion. Consistent with this rationale, catalysis by CD-0387 with 2-ME as cosubstrate, while less efficient, is not subject to potent inhibition by l-cysteine. The similarity of the maximum rate constant for persulfide cleavage by DTT to k cat suggests that persulfide cleavage is, in fact, primarily rate-determining, and this conclusion is confirmed by the observation that k cat is ∼10-fold greater when tris-(2-carboxyethyl)phosphine (TCEP), the most efficient persulfide cleaver identified, is used as the reducing cosubstrate. The faster turnover with TCEP provides a chemical model for activation of CD-0387 and other CDs by the presence of accessory factors that serve as efficient acceptors of the persulfide sulfur.